Social Support, Academic Satisfaction, and Student Drop Out Tendency/ Dukungan Sosial, Academic Satisfaction, dan Kecenderungan Drop Out pada Mahasiswa - Abdullah, Airlangga Wicaksono; Muhid, Abdul (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Abstract: The purpose of carrying out this research is to determine the relationship between social support and academic satisfaction with the tendency to drop out of students at UIN Sunan Ampel Surabaya. This research uses correlational quantitative method. Researchers used a Likert scale to measure social support and academic satisfaction with the tendency to drop out of students. With 135 subjects from a total population of 4467 students, researchers used the random sampling method to obtain the research sample. The data collection method used was a gform questionnaire (questionnaire). The method used to test the hypothesis is multiple linear regression analysis. The results of the regression analysis show that social support has no effect on the tendency to drop out. while academic satisfaction has a negative effect on the tendency to drop out.Keywords: Social Support; Academic Satisfaction; The Trend of Drop OutAbstrak: Tujuan dari dilaksanakannya penelitian ini adalah untuk mengetahui hubungan antara dukungan sosial dan academic satisfaction dengan kecenderungan drop out pada mahasiswa UIN Sunan Ampel Surabaya. Penelitian ini menggunakan metode kuantitatif korelasional. Peneliti menggunakan skala likert untuk mengukur dukungan sosial dan academic satisfaction terhadap kecenderungan drop out pada mahasiswa. Dengan subjek berjumlah 135 dari total populasi 4467 mahasiswa, peneliti menggunakan metode random sampling untuk mendapatkan sampel penelitian. Metode pengumpulan data yang digunakan adalah angket google form (kuesioner). Metode yang digunakan untuk uji hipotesis adalah analisis regresi linear berganda. Hasil analisis regresi menunjukan bahwa dukungan sosial tidak memiliki pengaruh terhadap kecenderungan drop out, sedangakan academic satisfaction memiliki pengaruh negatif terhadap kecenderungan drop out.Kata kunci: Dukungan Sosial; Kepuasan Akademik; Kecenderungan Drop Out